2020
DOI: 10.1126/sciadv.aav7523
|View full text |Cite
|
Sign up to set email alerts
|

An electrically pumped surface-emitting semiconductor green laser

Abstract: Ultrasmall semiconductor lasers can improve the efficiency and resolution of next-generation displays by 10 to 100 times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 83 publications
1
74
0
Order By: Relevance
“…also be readily achieved using photonic crystal structure designed to operate at Γ point. [74] Figure 7a shows the schematic of light scattering in the reciprocal space of a photonic crystal structure. Six Γ' points are coupled by the Bragg grating vectors K 1 and K 2 , which leads to standing wave resonant in the photonic crystal structure and eliminates the need for extra mirrors for optical feedback in the X-Y plane.…”
Section: Surface-emitting Laser Diodesmentioning
confidence: 99%
See 2 more Smart Citations
“…also be readily achieved using photonic crystal structure designed to operate at Γ point. [74] Figure 7a shows the schematic of light scattering in the reciprocal space of a photonic crystal structure. Six Γ' points are coupled by the Bragg grating vectors K 1 and K 2 , which leads to standing wave resonant in the photonic crystal structure and eliminates the need for extra mirrors for optical feedback in the X-Y plane.…”
Section: Surface-emitting Laser Diodesmentioning
confidence: 99%
“…Rreproduced under the terms of the Creative Commons CC-BY license. [74] Copyright 2020, AAAS. polarized emission.…”
Section: Aln and Algan Uv Leds And Laser Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Wang et al [343] recently reported a record-breaking net mode gain of up to 980 cm −1 in CsPbBr 3 nanorodbased gain media with a diameter of ∼5.8 nm and a length of ∼26 nm using an intermediate monomer reservoir synthetic strategy. Similarly, group-III nitrides have benefitted from low-dimensionality nanostructures such as the previously discussed QDs [314,378] and nanorods or nanowires [4,327,379].…”
Section: Low Dimensionality Nano/microstructuresmentioning
confidence: 99%
“…SAG is a combination of a top-down method for the nanoscale patterning of growth mask coupled with bottom-up epitaxy on the previously defined template used for creating regular arrays of NRs. The SAG process has been employed for the successful growth of III-nitride NR devices [18][19][20][21][22][23][24][25] and photonic crystal structures [26,27].…”
Section: Introductionmentioning
confidence: 99%